STEAM as a tool to encourage engineering studies - Oliveros Ruiz, Maria Amparo (Revista Científica, 2019)
In recent times women have been making their way into engineering, one of the most booming fields internationally. However, women enrollment in these careers in Mexico has grown slowly, only about 30 % of the total student population enrolled in an engineering related program are women. For the purposes of this research, a survey was applied to the students of three universities in the northwest region of Mexico confirmed a STEAM network aiming to promote enrollment, retention and gender equality on STEM careers, in order to present the outcome about their motivation for this career choice. As well as the future performance model of female students enrolled in engineering degrees. Findings have shown that there is no female model to follow, so it is proposed to include a Science, Technology, Engineering, Arts and Mathematics (STEAM) model in the Schools of Engineering to increase preference and enrollment of women in this area of knowledge.